Formation of Ester Bound 2‐ and 3‐MCPD and Esterified Glycidol in Deep‐Fried and Pickled Herring Products. Issue 7 (2nd May 2018) - Merkle, Sybille; Ostermeyer, Ute; Rohn, Sascha; Karl, Horst; Fritsche, Jan
Abstract : In Germany, the best‐selling fish products are canned and marinated fish products including deep‐fried and pickled herring products. During processing, pre‐salted herring fillets are breaded, deep‐fried, and covered by an aqueous marinade containing vinegar and sodium chloride. For shelf‐life extension, the packaged fish can be pasteurized. Due to the co‐occurrence of sodium chloride and glycerol derivatives such as tri‐ or diacylglycerides, the deep‐frying and pasteurization procedure may lead to the formation of fatty acid esters of 2‐monochloropropane‐1, 3‐diol and 3‐monochloropropane‐1, 2‐diol (MCPD‐E) and of glycidol (G‐E). Various product as well as process dependent parameters on the formation of MCPD‐E and G‐E in deep‐fried and pickled herring products are studied. The frying‐life of the oil has the strongest effect on the formation of MCPD‐E in herring products. 3‐MCPD‐E contents increases from 341 ± 48 to 1133 ± 194 μg kg −1 lipid in the products after 9 days frying‐life of the oil. Moreover, it is shown that the major proportion of MCPD‐E in these products originates from the deep‐frying oil. The analyses of total polar material and spectrophotometric measurement of the absorption at 420 nm of the deep‐frying oil are identified as suitable screening methods for estimating MCPD‐E contents in deep‐fried and pickled herring products. Practical Applications : Canned and marinated fish products are the best‐selling fish products (28% market share) on the German market. Up to now, no studies regarding the deep‐frying procedure of pickled herring products are published. Deep‐frying has shown to be a process leading to MCPD‐E and G‐E in fish products mainly affected by intake of deep‐frying oil. The knowledge about the effect of process and product based parameters on the formation of MCPD‐E and G‐E in deep‐fried and pickled herring products may be of particular interest for the fish‐processing industry in order to manage that quality issue. Moreover, methods for the assessment of the deep‐frying oil quality such as the analysis of the total polar material (TPM) and the spectrophotometric measurement of the absorption at 420 nm deemed suitable screening methods for estimating the MCPD‐E contents in deep‐fried and pickled herring products. Deep‐frying of pickled herring products leads to the formation of MCPD‐E and G‐E, mainly affected by intake of deep‐frying oil and the frying‐life of the oil. Methods for the assessment of the frying oil quality, such as the analysis of TPM and the spectrophotometric measurement of the absorption, are suitable screening methods for estimating the MCPD‐E contents in deep‐fried fish products. Abstract : Deep‐frying of pickled herring products leads to the formation of MCPD‐E and G‐E, mainly affected by intake of deep‐frying oil and the frying‐life of the oil. Methods for the assessment of the frying oil quality, such as the analysis of TPM and the spectrophotometric measurement of the absorption, are suitable screening methods for estimating the MCPD‐E contents in deep‐fried fish products.